Regulation theory and development planning: the case of southern Pinetown, Kwazulu-Natal - Werkman, Anthony James (My University, 1995)
Development planning plays an important role in integrating the actions and behaviours of groups and individuals with the needs of the economy. and thus in ensuring the continued reproduction of capitalism. An understanding of the history of development planning in South Africa and in Southern Pinetown through the tools of regulation theory, shows how the apartheid "development planning process' for a limited amount of time, arguably favoured the needs of racially skewed capital by securing stability and control over an exploited, black workforce, Within the post apartheid era characterised by constant and unprecedented change, development planning needs to become impregnated within the fabric of society. The role for planners and the local state is therefore to impart a strategic planning mind set into the diverse forces and components, whose combined actions together create the urban form.
A discourse submitted to the Faculty of Town and Regional Planning, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for Master or Science in Development Planning.
Keywords: Development economics.; Pinetown (South Africa) -- Economic conditions.